2020
DOI: 10.1186/s12885-020-07121-8
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic vaccinia virus GLV-1h68 exhibits profound antitumoral activities in cell lines originating from neuroendocrine neoplasms

Abstract: Background: Oncolytic virotherapy is an upcoming treatment option for many tumor entities. But so far, a first oncolytic virus only was approved for advanced stages of malignant melanomas. Neuroendocrine tumors (NETs) constitute a heterogenous group of tumors arising from the neuroendocrine system at diverse anatomic sites. Due to often slow growth rates and (in most cases) endocrine non-functionality, NETs are often detected only in a progressed metastatic situation, where therapy options are still severely l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…When studying the viral growth kinetics of MeV-SCD in the presence and absence of everolimus in NEN tumor cells, we did not observe altered virus growth. Interestingly, in another study using the oncolytic vaccinia virus GLV-1h68, everolimus also neither impaired nor enhanced viral replication in NEN cells [29]. The same results were obtained for the later-discussed oncolytic herpes simplex virus talimogene laherparepvec (T-VEC) [28].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…When studying the viral growth kinetics of MeV-SCD in the presence and absence of everolimus in NEN tumor cells, we did not observe altered virus growth. Interestingly, in another study using the oncolytic vaccinia virus GLV-1h68, everolimus also neither impaired nor enhanced viral replication in NEN cells [29]. The same results were obtained for the later-discussed oncolytic herpes simplex virus talimogene laherparepvec (T-VEC) [28].…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the vaccinia virus GLV-1h68 has also been shown to reduce several NET and NEC cell lines in a dose-dependent manner: three of them proved to be highly permissive towards the chosen criteria, three were defined as intermediate permissive, and no resistant NEN cell line was found, which has been interpreted as a pretty good result [29].…”
Section: Introductionmentioning
confidence: 99%
“…Talimogene laherparepvec is a first-generation, state-of-the-art HSV-1-based oncolytic virus that does not integrate its viral DNA into the host genome and that shows high oncolytic efficacy at low concentrations when applied to NETs and NECs [ 105 ]. GLV-1 h68 relies on vaccinia viruses that also do not disturb the host genome and have a good oncolytic effect against NETs and NECs [ 106 ].…”
Section: Microbial Communitymentioning
confidence: 99%
“…The Lauer group demonstrated that GLV-1h68, which includes three expression cassettes encoding β-glucuronidase, β-galactosidase and green fluorescent protein (GFP), exhibits stable cytotoxicity in human NET cells of various anatomical origins and also a highly efficient production of progeny virus particles. Moreover, additional combination with the mTOR inhibitor everolimus, which is approved for treatment of metastatic NETs, did not impair replication of GLV-1h68 suggesting that combinatorial treatment is not an obstacle for further development of the approach [ 73 ].…”
Section: Recent Preclinical Virotherapy Research Activities In Germanymentioning
confidence: 99%